MAKE A MATCH LEARNING MODEL TO IMPROVE LEARNING OUTCOMES FOR THE IV GRADE STUDENTS OF SDN 3 KARANGANOM - Isna Rahmawati; Nela Rofisian (Indonesian Journal of Elementary Teachers Education, 2022)
Study aims to improve student learning outcomes by using the make a match learning model in class IV SDN 3 Karanganom Utara Klaten. This research is a class action research with a cycle model from Kemmis Taggart. This research was conducted in six meetings in two cycles. Data collection techniques used observation, interviews, test results, documentation, and field notes. The instruments used were observation sheets, interview guidelines, test sheets, and field notes.The results showed the average student learning outcomes increased after learning improvements were made by applying the make a match learning model. In cycle 1 the average value of student learning outcomes increased to 77.9. Then in cycle 2 the average value of student learning outcomes increased to 80.6.